Kazakh Senate Ratifies Deal With China To Exchange Citizens' Personal Data - RFE/RL's Kazakh Service (RadioFreeEurope/RadioLiberty, 2023)
Amid concerns of rights watchdogs, the Kazakh Senate ratified on October 5 an agreement with China on the exchange of personal data of their citizens.
Kazakhstan
Keywords: 2023-10 October